Dampak Negatif yang Berhubungan dengan Penggunaan Double J Stent pada Pasien Batu Ureter - Simanjuntak, Dikes; Pahria, Tuti; Platini, Hesti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify the negative impact of using the Double J Stent (DJ stent) in patients with urinary tract stones. The method used is a Scoping Review using the Arksey & O'Malley (2005) framework through the Science Direct, Pubmed, and Scopus databases in the last five years (2017-2022). The research results showed ten articles identified the negative impact of DJ stent installation after ureteroscopy (URS), including pain, Lower Urinary Tract Symptoms (LUTS), urinary tract infections, sexual dysfunction, and decreased physical activity. In conclusion, the negative impact of DJ stent installation causes morbidity and reduces quality of life. Keywords: Ureteral stones, Impact, DJ Stent, Ureteroscopy